Human Activities Introduced Degenerations of Wetlands (1975–2013) across the Sanjiang Plain North of the Wandashan Mountain, China - Jing Xie; Yeran Sun; Xiao Liu; Zhi Ding; Ming Lu (Land, 2021)
Human-induced dramatic loss and fragmentation of wetlands need further understanding through historical backtracking analysis at a geographical landscape scale. In this study, we investigated time-series wetlands maps from 1975, 1983, 1989, 2000, 2006, and 2013 derived from Landsat images based on the object-oriented classification of wetlands across the Sanjiang Plain north of the Wandashan Mountains. The spatial and temporal changes in the wetlands that occurred at different time periods and the Euclidean distances between artificial land-use types and natural land-cover areas were evaluated for their impact. Our results showed that wetland was the dominant landscape in 1975; however, arable land became the main land coverage in 2013 owing to severe changes in agricultural development over the past decades. The closer to arable land, the greater the wetland loss during the entire investigated period; agriculture activities were the dominant driving force for the degradation of wetlands based on landscape changes; secondary was the rapid expansion in building land use (i.e., human settlement, transportation, and establishment of irrigation canals). More specifically, the rapid loss of wetland areas over 1975–2000 was mainly owing to extensive agricultural reclamation. The mitigated loss of wetland areas over 2000–2013 was because of the protection and restored implementation of wetlands under governmental policies. The wetlands of the study area suffered severe human disturbance, and our analysis may help explain the loss process of wetlands, but more effective management and administration is still needed to address the issues around the balance between agricultural production and wetland protection for further sustainable development.